The Peningkatan Perkembangan Sosial Emosional Melalui Media Buku Cerita Bergambar pada Anak Usia Dini di RA Miftahul Falah Gondosuli - Nanik Dwiyanti (Yayasan Azhar Amanaa Yogyakarta, 2026)
Findings: The results of the research showed that the child's emotional and social development before using picture storytelling media still requires guidance from the teacher to interact with others. After using image storyline media, the child better understands social relationships with friends, such as friendship relationships, and the child's desire to be loved is increased. The problem with the use of picture storytelling media is that teachers are still rigid and less creative in using story media, and children are more likely to joke and not listen to teacher explanations. Training is needed so teachers can be more skilled at telling stories, encouraging children to do icebreaking when they are bored with learning, and using additional audio-visual learning media to attract children's attention.